2019
DOI: 10.1007/s00426-019-01263-6
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and affective Theory of Mind in adolescence: developmental aspects and associated neuropsychological variables

Abstract: Theory of Mind (ToM) is the ability to represent and attribute mental states to oneself and others. So far, research regarding ToM processing across adolescence is scarce. Existing studies either yield inconsistent results or did not or not thoroughly investigate aspects like higher order ToM and associated neuropsychological variables which the current study tried to address. 643 typically developing early, middle, and late adolescents (age groups 13-14; 15-16; 17-18) performed cognitive and affective ToM tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 64 publications
(139 reference statements)
3
28
0
Order By: Relevance
“…Since the position of the protagonists on the last slide of each trial in combination with their eye gazes is essential to deduce their respective thoughts and beliefs, an association with this previously discovered posterior slow wave seems reasonable. Supporting this notion, previous studies indicated an association between visual-spatial mentalization/visual perspective taking and ToM processing (e.g., Gabriel et al, 2019) and shared neuronal activation regarding these abilities as for example in the left TPJ, the PCC, and the precuneus (Schurz et al, 2013).…”
Section: Discussionmentioning
confidence: 65%
“…Since the position of the protagonists on the last slide of each trial in combination with their eye gazes is essential to deduce their respective thoughts and beliefs, an association with this previously discovered posterior slow wave seems reasonable. Supporting this notion, previous studies indicated an association between visual-spatial mentalization/visual perspective taking and ToM processing (e.g., Gabriel et al, 2019) and shared neuronal activation regarding these abilities as for example in the left TPJ, the PCC, and the precuneus (Schurz et al, 2013).…”
Section: Discussionmentioning
confidence: 65%
“…Changes in social processes (including social cognition) may also be influenced (directly and indirectly, through brain development) by puberty‐related factors (Pfeifer & Allen, 2021), with changing impact from early through middle to late adolescence. Coherently, there is also evidence for the age‐related differences in advanced ToM, as measured with story‐based tasks, between early and middle adolescence (Gabriel et al, 2021).…”
Section: Advanced Theory Of Mind and Its Measurementmentioning
confidence: 99%
“…In contrast, sex differences in ToM appear controversial. While in some studies males and females had the same performance on ToM tasks (Di Tella et al, 2020), in other studies females had better performance compared with males during preschool and elementary school years (Charman et al, 2002;Walker, 2005;Calero et al, 2013), adolescence (Gabriel et al, 2021), and adulthood (Wacker et al, 2017).…”
Section: Theory Of Mind and Hrv: The Present Studymentioning
confidence: 92%